Integrating traditional Chinese medicine healthcare into dementia care plan by reducing the need for special nursing care and medical expenses. Issue 7 (February 2019) - Lin, Shun-Ku; Lo, Pei-Chia; Chen, Wang-Chuan; Lai, Jung-Nien
Abstract : Abstract: Reducing the need for advanced nursing care and medical expenses is an essential concern of dementia care. We investigated the impact of traditional Chinese medicine (TCM) on advanced nursing care and medical costs. We used Longitudinal Health Insurance Database to implement a cohort study of patients with dementia between 1997 and 2012 in Taiwan. Data from the onset of dementia to 1st advanced nursing care for the endotracheal tube, urinal indwelling catheterization, and nasogastric tube were assessed using Cox regression proportional hazards model, and independent t test was used to determine the difference of hospitalization costs and days. We also used ANOVA test to compare the hospital cost, hospital stay, and numbers according to different duration of TCM. We assessed 9438 new diagnosed patients with dementia without advanced nursing care were categorized into 2 groups: 4094 (43.4%) TCM users, and 5344 (56.6%) non-TCM users. In the TCM groups, 894 (21.8%) patients were declared as advanced nursing care, while 1683 (31.5%) patients were in non-TCM group. Cox proportional hazard regression indicated that using TCM may decrease the need for advanced nursing care (adjusted hazard ratio (aHR) = 0.61, 95% confidence interval [95% CI]: 0.56–0.66) compared to non-TCM. The TCM users have lower hospitalization costs and hospitalization time compared to non-TCM users. Integrating TCM healthcare into dementia care was found to be associated with a lower need for advanced nursing care, hospitalization costs, and admission time with more benefits from longer durations of TCM use.